Graduate employment in the UK: an application of the Gottschalk-Hansen model - Suzanne Grazier; Nigel C. O'Leary; Peter J. Sloane (Institute for the Study of Labor (IZA), 2008)
There is an apparent inconsistency in the existing literature on graduate employment in the UK. While analyses of rates of return to graduates or graduate markups show high returns, suggesting that demand has kept up with a rapidly rising supply of graduates, the literature on over-education suggests that many graduates are unable to find employment in graduate jobs and the proportion over-educated has risen over time. Using a simple supply and demand model applied to UK data that defines graduate jobs in terms of the proportion of graduates and/or the graduate earnings markup within occupations, we find that the employment of graduates in non-graduate jobs has declined over time. Hence, there is no evidence of an over-production of graduates in the UK.
urn:nbn:de:101:1-2008080780
Keywords: I2; 330; Education; wages; employment; graduates; Qualifikation; Bildungsertrag; Überqualifikation; Hochqualifizierte Arbeitskräfte; Arbeitsmarkt; Matching; Großbritannien